SEMANTICS AND PHILOSOPHY OF LANGUAGE IN TRANSLATION PRACTICE - Engliana, Engliana (Language Circle: Journal of Language and Literature, 2016)
This writing is conducted to demonstrate the interrelationship between the concepts of semantics and philosophy of linguistics and its implication in translation discipline. The writer starts by pointing out methods and emphasis of semantics and translation theories, although the writer will specifically discuss the practice of semantics in translating semantic situation. There are three parts of discussions in this paper: part one is mainly discussed the semantic and translation theories, part two describes the relation between the two subjects, and finally, part three shows the readers of how the semantics take place in translating written language. The writer finally wishes that the readers, especially Indonesian translators, will take benefit of understanding the semantics and use it for the benefit of as well as to denote and solve the problems and barriers in practicing translation.